Non-Economic Aspects of Academic Morale - Hughes, Everett C. (The Review of Economics and Statistics, 1960)
Everett C. Hughes, Non-Economic Aspects of Academic Morale, The Review of Economics and Statistics, Vol. 42, No. 3, Part 2. Higher Education in the United States: The Economic Problems (Aug., 1960), pp. 118-121